Formed MoVTeTaOx and MoVTeNbOx catalysts with high strength and ODH performance
Fumed silica-based molding catalysts with a MoVTeTaOx catalytic active phase enhance the efficiency of ethane conversion to ethylene in oxidative dehydrogenation, overcoming the challenges of energy costs and conversion rates in existing methods.
Patent Information
- Application Number
- JP2024557973
- Authority / Receiving Office
- JP · JP
- Patent Type
- Applications
- Current Assignee / Owner
- Priority Date
- 2022-04-01
- Filing Date
- 2023-03-08
- Publication Date
- 2025-04-15
AI Technical Summary
Current methods for converting lower alkanes to olefins, such as steam decomposition and selective oxidation processes like oxidative dehydrogenation (ODH), face challenges including high energy costs, coke formation, and lower conversion and selectivity rates in ODH.
Development of fumed silica formulations that produce molding catalysts with high mechanical strength for oxidative dehydrogenation (ODH) of ethane, using a catalytically active phase of MoVTeTaOx and a support phase of fumed silica, along with binders, plasticizers, and lubricants to enhance performance.
The catalysts exhibit excellent activity and ethylene selectivity while maintaining high mechanical strength, addressing the limitations of existing technologies by improving conversion rates and reducing energy costs.
Smart Images

Figure 2025511153000001_ABST
Abstract
Description
[Technical field]
[0001] This document relates to heterogeneous shaped catalysts, methods for the synthesis of said catalysts, and methods for the use of said catalysts. [Background technology]
[0002] Olefins, such as ethylene, propylene, and butylene, are the basic building blocks of a variety of commercially valuable polymers. Because naturally occurring sources of olefins do not exist in commercial quantities, polymer producers rely on methods to convert the more abundant lower alkanes into olefins. The method of choice for commercial-scale producers today is steam cracking. Steam cracking is a highly endothermic process that briefly exposes alkanes diluted with steam to temperatures of at least 800 °C. The fuel demand to generate the required temperatures, and the need for equipment that can withstand those temperatures, significantly increase overall costs. In addition, high temperatures promote coke formation, which accumulates in the system, necessitating costly periodic reactor shutdowns for maintenance and coke removal.
[0003] Selective oxidation processes such as oxidative dehydrogenation (ODH) are alternatives to steam cracking that are exothermic and produce little or no coke. In ODH, lower alkanes such as ethane are mixed with oxygen in the presence of a catalyst and, optionally, an inert diluent (e.g., carbon dioxide, methane, nitrogen, or steam) to produce the corresponding alkenes at temperatures as low as 300 °C. A variety of other oxidation products may be produced in the process, including carbon dioxide and acetic acid, among others. ODH suffers from lower conversions compared to steam cracking, which, combined with low selectivity and the risk of thermal explosion due to mixing of hydrocarbons with oxygen, may prevent commercial widespread use of ODH.
[0004] Shaped catalysts can be used for the ODH of ethane. Shaping is important when making heterogeneous catalysts. For fixed bed catalysts, the shape of the catalyst material facilitates many important things such as pressure drop across the reactor, heat and mass transfer, avoidance of fines during packing and handling, catalyst attribution / decomposition during process operation, and catalyst cost. Summary of the Invention
[0005] This disclosure describes fumed silica formulations that produce shaped catalysts with very high mechanical strength while maintaining excellent performance as measured by activity and ethylene selectivity in the oxidative dehydrogenation of ethane (ODH).
[0006] In one embodiment, a composition is provided that includes a catalytically active phase, the catalytically active phase comprising a MoVTeTaOx catalyst, the composition also including a support phase, the support phase comprising fumed silica, and the catalytically active phase and the support phase form a heterogeneous mixture.
[0007] In one embodiment, the composition includes a binder, the binder includes a polymeric organic acid, an amine, or an alcohol. In one embodiment, the binder includes polyvinyl alcohol or polyethylene glycol, or both. In one embodiment, the binder includes 60-80 wt% polyvinyl alcohol and 20-40 wt% polyethylene glycol.
[0008] In one embodiment, the composition further comprises an inorganic binder, the inorganic binder comprising talc or calcium carbonate.
[0009] In one embodiment, the composition is sintered to form a ceramic.
[0010] In one embodiment, the composition further comprises a plasticizer, wherein the plasticizer comprises polyethylene glycol.
[0011] In one embodiment, the composition further comprises a lubricant, hi one embodiment, the lubricant is 1-2 wt% of the composition, and the lubricant comprises graphite.
[0012] In one embodiment, the fumed silica is 5-95 wt% of the composition.
[0013] In one embodiment, the composition is formed into a pressed tablet, the pressed tablet having a density of 1.0 to 1.5 g / cm 3 has a density of
[0014] In one embodiment, the composition is formed into a sintered ceramic catalyst.
[0015] Another embodiment described herein provides a method for producing a shaped catalyst. The method includes combining a catalytically active phase, a support phase, and a binder in an aqueous solvent to form an aqueous solution, where the catalytically active phase includes MoVTeTaOx and the support phase includes fumed silica. The method also includes heating the aqueous solution to form a thick paste, drying the thick paste to evaporate the aqueous solvent and form a solid powder, grinding the solid powder to form granules, and compressing the granules to form a tablet.
[0016] In one embodiment, the step of milling the solid powder to form granules comprises milling the solid powder to form granules, the granules having a diameter between 105 μm and 710 μm.
[0017] In one embodiment, the method further comprises the steps of debinding the tablet, which comprises heating the tablet to remove the binder, and sintering the tablet, which comprises heating the tablet to coalesce into a densified solid. In one embodiment, debinding the tablet comprises heating the tablet to 200°C-400°C at a rate of 1-2°C / min. In one embodiment, sintering the tablet comprises heating the tablet to 400°C-600°C at a rate of up to 5°C / min.
[0018] Another embodiment described herein provides a method for producing a shaped catalyst. The method includes combining a catalytically active phase, a support phase, and a binder in an aqueous solvent to form an aqueous solution, where the catalytically active phase includes MoVTeTaOx and the support phase includes fumed silica, and includes heating the aqueous solution to form a thick paste, and drying the thick paste to evaporate the aqueous solvent and form a solid powder. The solid powder is ground to form granules, and the granules are compressed to form a tablet. The method further includes debinding the tablet, which includes heating the tablet to remove the binder, and sintering the tablet, which includes heating the tablet to coalesce into a densified solid.
[0019] Another embodiment described herein provides a method for oxidative dehydrogenation of ethane. The method includes flowing a feed gas to a microreactor unit, the feed gas comprising ethane, oxygen, and nitrogen, pressurizing the feed gas in the microreactor, and contacting the feed gas with a shaped catalyst. The shaped catalyst includes a catalyst active phase comprising MoVTeTaOx catalyst and a support phase comprising fumed silica, the catalyst active phase and the support phase forming a heterogeneous mixture. The method includes heating the feed gas to 450° C. to 470° C. and recovering ethylene gas.
[0020] In one embodiment, the feed gas has a molar ratio of ethane to oxygen of 1:0.5.
[0021] The details of one or more embodiments of the disclosure are set forth in the accompanying drawings and the description below. Other features, objects, and advantages of the disclosure will become apparent from the description and drawings, and from the claims. [Brief description of the drawings]
[0022] [Figure 1] 1 shows an example of a schematic diagram of a shaped catalyst. [Diagram 2] An example of a method for forming a shaped catalyst is shown below. [Diagram 3] FIG. 1 shows a flow diagram of an example process for debinding and sintering a catalyst. [Figure 4] 1 is a flow chart of an example process for oxidative dehydrogenation of ethane. [Diagram 5] 1 shows the tabletting profile of molded catalyst 1.5 green tablets (molded catalyst 1.5GB). [Figure 6] 1 shows the tabletting profile of molded catalyst 1.7 green tablets (molded catalyst 1.7GB). [Figure 7] 1 shows the tabletting profiles of comparative molded catalyst 2.1GB tablets and comparative molded catalyst 2.2GB tablets. [Figure 8] 1 shows the MRU data for long-term ethane to ethylene conversion of molded catalyst 1.2SB tablets containing only MoVTeTaOx catalyst. [Figure 9] The results of a long-term ethylene selectivity test of molded catalyst 1.2SB tablets are shown. [Figure 10] 1 shows the conversion MRU data plot of MoVTeTaOx supported shaped catalyst 1.3SB tablet. [Figure 11] 1 shows the selectivity MRU data plot for MoVTeTaOx supported shaped catalyst 1.3SB tablets. [Figure 12] 1 shows the conversion MRU data plot of MoVTeTaOx supported shaped catalyst 1.5SB tablet. [Figure 13]1 shows the selectivity MRU data plot for MoVTeTaOx supported shaped catalyst 1.5SB tablets. [Figure 14] The results of a long-term ethane conversion test of molded catalyst 1.7SB tablets are shown. [Figure 15] The results of a long-term ethylene selectivity test of molded catalyst 1.7SB tablets are shown. [Figure 16] 4 shows the long-term ethane conversion of shaped catalyst 1.8SB tablets. [Figure 17] 4 shows the ethylene selectivity of molded catalyst 1.8SB tablets. [Figure 18] Long term ethylene selectivity testing of shaped catalyst 1.7SB and shaped catalyst 1.8SB are overlaid on one plot.Like reference symbols in the various drawings indicate like elements. DETAILED DESCRIPTION OF THE PREFERRED EMBODIMENTS
[0023] Reference will now be made in detail to certain embodiments of the disclosed subject matter, examples of which are illustrated in part in the accompanying drawings. While the disclosed subject matter will be described in conjunction with the enumerated claims, it will be understood that the illustrated subject matter is not intended to limit the claims to the disclosed subject matter.
[0024] Provided in this disclosure are, in part, compositions and methods for converting ethane to ethylene. The compositions include a shaped catalyst, i.e., a mixture of heterogeneous catalyst components that can be compressed into a predetermined shape, e.g., a cylindrical shape. The shaped catalyst includes a catalytically active phase, a support, and a binder. The catalytically active phase is the component responsible for catalyzing the conversion of ethane to ethylene in the presence of oxygen. In some embodiments, the catalytically active phase includes a MoVTeTaOx catalyst. The MoVTeTaOx catalyst includes molybdenum (Mo), vanadium (V), tellurium (Te), tantalum (Ta), and oxygen (O). The catalyst is represented by the formula MoVTeTaOx. In some embodiments, the ratio of elements in the catalytically active phase is Mo1V 0.66 Te 0.17 Ta 0.09In some embodiments, the ratio of elements in the catalytically active phase is Mo1V 0.31 Te 0.22 Ta 0.10 Ox. In some embodiments, the catalytically active phase comprises a MoVTeNbOx catalyst.
[0025] The support in the shaped catalyst is important for the properties of the resulting shaped catalyst. For example, the support can facilitate the shaping of the supported catalyst, increase the mechanical strength, avoid fines during packing, prevent catalyst attrition during process operation, and can be one of the ways to reduce the overall cost of the shaped catalyst. The shape and support of the catalyst can also improve heat and mass transfer, providing pores and channels that allow gas products to enter and exit the shaped catalyst, and facilitating heat transfer from the catalyst and reactants. In addition, the shape and size of the shaped catalyst can affect the pressure drop design across the reactor. The support can also reduce the overall cost of producing the shaped catalyst by dispersing the catalyst particles through the support and allowing the reactants to easily access the active sites. Thus, the support plays several roles in the shaped catalyst. Examples of supports / catalyst supports include precipitated silica, fumed silica, and alpha alumina. The shaped catalysts described herein are synthesized using fumed silica.
[0026] The shaped catalysts herein include fumed silica formulations that support the catalyst and produce shaped catalysts with very high mechanical strength, while maintaining excellent performance as demonstrated by activity and ethylene selectivity in the oxidative dehydrogenation of ethane.
[0027] The addition of the support to the catalyst tablet improved the overall catalyst performance compared to the catalyst-only tablet. This was a surprising result. Without wishing to be bound by theory, it is believed that the improved performance of the shaped catalyst is due to the improved ability of the feed gas to access all catalyst particles within the shaped catalyst tablet, despite the shaped catalyst being densely packed. In theory, the lack of porosity increases the density of the catalyst tablet with high mechanical strength. However, by including a silica support in the catalyst, the catalyst maintains some porosity without compromising mechanical strength. In addition to high mechanical strength, shaped catalysts containing fumed silica exhibit new material properties due to the inclusion of a fumed silica support. Typically, silica is a difficult material to expand (aggregate) into mechanically strong macro shapes. For example, it is difficult to aggregate silica into shapes larger than 200 μm that are typical of spray-dried silica applied to other heterogeneous technologies such as gas phase polyethylene production. However, as described herein, catalysts containing fumed silica with an oxidative dehydrogenation catalytically active phase result in catalyst materials with unique properties that are different from fumed silica alone. Molded catalysts with fumed silica support materials have processing properties that are superior to other tablet compressed ceramic materials such as alumina. This property is illustrated by a comparison of the tabletability profiles, i.e., the radial tensile strength of the tablets as a function of compression pressure. The tabletability profiles are described in Examples 2 and 3 herein. Furthermore, the catalyst tablets described herein have significantly higher density and mechanical strength, as shown in Examples 5 and 6.
[0028] The shaped catalysts described herein also include a binder. A binder in the shaped catalysts described herein is an additive that aids in cohesion and makes the overall mixture more moldable. In some embodiments, an organic additive can be used as a binder. Suitable organic binders include polymeric organic acids, amines, or alcohols (e.g., polyvinyl alcohol) that can enable crosslinking or particle formation. In some embodiments, an inorganic binder can be used. Suitable inorganic binders include soft (low Mohs hardness values) salt minerals (e.g., talc or calcium carbonate). In some embodiments, the binder can be a mixture of two or more binders. For example, the binder can include a mixture of polyvinyl alcohol (PVA) and polyethylene glycol (PEG). In some embodiments, the binder includes 80 wt% PVA and 20 wt% PEG. In some embodiments, the binder includes 60 wt% PVA and 40 wt% PEG.
[0029] In some embodiments, the shaped catalyst may include a plasticizer, a lubricant, or both a plasticizer and a lubricant. A plasticizer is an additive that acts on an organic binder. The combination of an organic binder and a plasticizer is more plastic than the two components used separately. The amount and type of plasticizer can be selected based on the ability of the plasticizer to lower the glass transition temperature of the polymer binder. In some embodiments, the plasticizer can include polyethylene glycol.
[0030] In some embodiments, the shaped catalyst also includes an intergranular or intragranular lubricant, which is an additive added to granular powders to make the compacted form easier to remove from the die cavity and can prevent clogging and excessive wear on equipment.
[0031] 1 shows an example of a schematic diagram of a shaped catalyst 100. The shaped catalyst 100 can include active phase catalyst particles 102, support particles 104, a binder 106, an intergranular lubricant 108, and an intragranular lubricant 110. The shaped catalyst 100 can include any combination of features 102-110, but does not necessarily require all features 102-110. For example, the shaped catalyst 100 can include active phase catalyst particles 102, support particles 104, and a binder 106.
[0032] The shaped catalysts described herein can be used to catalyze the oxidative dehydrogenation of ethane, which is shown in Equation 1.
number
[0033] In some embodiments, the shaped catalysts described herein include a MoVTeTaOx active catalyst phase. In some embodiments, the shaped catalysts described herein include a MoVTeNbOx active catalyst phase. Comparative examples of shaped catalysts without an active catalyst phase or with an alternative support phase were also produced. The formulations of the shaped catalysts analyzed in Examples 1-11 are shown in Table 1. The silica support in Table 1 is fumed silica. However, in some embodiments, the silica may be other forms of silica. For example, precipitated silica (hydrated), fumed silica (small size dehydrated), or colloidal silica (small size hydrated), or any mixture thereof, may be used as the silica support. The silica support may be 5-95 wt% of the composition. In some embodiments, the silica is 40-80 wt% of the composition. In some embodiments, the tablets include an intragranular lubricant. The lubricant was applied by dry mixing by hand tumbling in a drum for 5 minutes. The shaped catalysts described herein and in Table 1 were synthesized using wet blending, briquetting, granulation, and tablet compression, as described in more detail herein. FIG. 2 shows an example 200 of a method for forming a shaped catalyst. At 202, a catalytically active phase, a support phase, and a binder are combined in an aqueous solvent to form an aqueous solution. At 204, the aqueous solution is heated to form a thick paste. At 206, the thick paste is dried to evaporate the aqueous solvent and form a solid powder. At 208, the solid powder is crushed to form granules. At 210, the granules are compressed (pressed) to form a tablet. In some embodiments, the method further includes debinding and sintering the tablet. Methods for forming shaped catalysts are described in more detail herein.
[0034] <Wet Formulation> The synthesis of shaped catalysts involves wet blending. The ingredients added to the blend to produce a moldable composition depend both on the particular molding process used (e.g., tablet press or extrusion) and the properties to be incorporated into the final molded shape. Shape, processing equipment, and composition must all be considered during the catalyst blend selection stage. Judicious selection of ingredients (e.g., binders and lubricants) affects how the wet or dry powder clumps together, is processed through equipment, compresses under force, sinters, and resists abrasive / crushing forces. Furthermore, composition and shape have a critical impact on the catalyst's final performance. In addition to meeting the requirements of the intended process unit, shape and composition must also impart sufficient mechanical properties to withstand transportation, loading into the reactor, handling, and removal from the reactor.
[0035] To convert the material into a moldable composition, the ingredients are blended into a uniform distribution to produce a homogenous mixture of catalyst ingredients. The ingredients of the shaped catalysts described herein were wet blended into a uniform paste, which was then dried and processed into granules. In the wet blending process, the ingredients are mixed and the agglomeration process is initiated. The shaped catalysts described herein were wet blended using bench-top mixing equipment (e.g., beaker, oil bath, low shear overhead stirrer). The wet blending was done under heat and mixing to evaporate excess water and convert the suspension of ingredients into a homogenous paste. The paste was then dried overnight in an oven at 105-110°C.
[0036] <Briquetting / Agglomeration> After drying overnight, the resulting dried "cake" was crushed in a mortar and pestle and fed into a 40 mm diameter die set to form briquettes in a press. 7 g of blend powder was placed in the 40 mm die set and pressed with a force of 12 tons and held at this force for 60 seconds. The force applied to the blend powder is a function of cross-sectional area, so sufficient force must be used to create powder agglomeration depending on the size of the briquette. Briquettes can be formed in a press. Alternatively, briquetting and granulation can be done in a high shear mixer. The disk-shaped briquettes produced were extracted. Granules were produced from the briquettes by crushing the briquettes into particles and sieving the particles to obtain the desired particle size distribution.
[0037] <Granulation> The key step in tablet compression (tablet press) is the conversion of fine powders of the individual components of the shaped catalyst into cohesive particles of increased size. This process is called granulation. Granulation is important for several reasons:
[0038] Granulation improves the flow properties of the material, allowing it to flow from the hopper into the die cavity. The flowability of ceramic powders can be defined and measured using definitions and methods available in ASTM D6103 / D6103M. Powders with particle sizes that are too small can cause "clumping," where the particles do not flow smoothly past one another. Agglomeration of small particles can be caused by electrostatic charges and increased van der Waals interactions due to increased surface area relative to volume. These forces can overcome the force of gravity acting on the particles. Additionally, granulated particles are more compressible than unmodified fine powders, resulting in tablets with higher densities and uniform density. Without wishing to be bound by theory, granules exhibit higher compressibility than fine powders because granules can plastically deform and / or break during rearrangement of granulated particles when compressed uniaxially. Plastic deformation and / or breakage allows granules to fill voids and increase intergranular contact with other particles.
[0039] Granule particle size distribution has been found to affect the mechanical strength of tablets, especially those produced using the automatic loading mode of automatic tablet press equipment. Therefore, a study was conducted to determine how different granule particle size distributions affect the crushing strength of automatically loaded tablets.
[0040] <Compression (Pressing)> As described herein, shaped catalysts are formed using tablet compression (uniaxial die press or dry press).
[0041] Tablets formulated as described in Table 1 were produced using a CPR-6 automatic press from DOTT.BONAPACE&C.SRL (Milan, Italy) or a CARVER® manual press from Carver, Inc. (Wabash, Indiana, USA). The CPR-6 automatic press is equipped with an adjustable force of up to 2.5 metric tons and interchangeable diameter die sets. The die set used herein was a cylindrical cavity with a 0.125 inch (3.175 mm) outer diameter with a flat-faced punch. The tablets were formed by a compound pressing action of two punches in the die. In the first step of the pressing operation, the lower punch is lowered in the die to form a cavity into which the catalyst material powder is fed via a hopper shoe. The exact depth of the lower punch is precisely set to meter the amount of powder to be filled into the cavity. The excess is scraped off the top of the die by the hopper shoe. The upper punch is then lowered into contact with the powder and a compression force is applied by the high pressure compression rolls, compressing the catalyst materials together into a hard pellet of the ideal shape. After the compression step, the lower punch is raised to eject the pellet from the die cavity. Finally, the tablet is pushed out of the tablet press stage by the hopper shoe during the subsequent filling of the die cavity. The pellets are knocked out of the stage into a collection pan.
[0042] Compression force can be adjusted by moving the top die up or down. The top die set incorporates settings from 1 to 8, with 8 being the highest compression force. Compression forces ranged from 520MPa to 1040MPa. Additionally, adjustments to the bottom die also change the resulting linear displacement, which can affect the final compression force. The bottom die can be screwed up or down to make the final tablet height shorter (more compression) or taller (less compression). The bottom die can be labeled with three settings: "1", "2", and "3". The bottom die setting 3 is the highest compression force and 1 is the lowest compression force. Since compression is a function of the tablet formulation itself, the top and bottom dies can be adjusted for each formulation.
[0043] The autopressor speed can also be adjusted. At lower speeds, the compressed material will shape and conform to the die set, making the tablets stronger and less prone to "capping", where the top and bottom of the tablet separate horizontally from the body. However, the autopressor speed should be fast enough to provide sufficient throughput. A speed setting of "2" has been found to produce tablets with high crushing strengths for a variety of formulation materials. This speed can be adjusted depending on the equipment used to make the tablets.
[0044] In some embodiments, the tablets can be formed using a CARVER press. The CARVER press is a manual press equipped with a force reading gauge that can form tablets under different compression forces. The CARVER press can be used to form tablets with a diameter of 6 mm.
[0045] Compression of the blended granules results in green tablets that are not debindered or sintered. The green tablets are analyzed to obtain a tabletability profile. The tabletability profile can be used to compare the response of granule blends to compression, with an ideal material having an increasing tensile strength as the compression pressure increases. The tensile strength of an ideal blend increases with compression pressure until a maximum tensile strength is reached, after which additional compression pressure does not improve the mechanical strength.
[0046] The tabletability profile can also be used to interpolate the compression pressure required to achieve green tablets with sufficient strength (i.e., tensile strength of at least 1-2 MPa). As described herein, the strength of the green tablets must be high enough to allow the tablets to be discharged intact from the tablet press and to withstand subsequent handling prior to the debinding and sintering steps. The axial and radial crushing strengths of the molded catalysts and comparative examples are described in Examples 2-5. The tensile strength used in the tabletability profile is typically calculated based on the radial crushing strength.
[0047] When comparing tablets of different sizes, the crushing strength (breaking force, in Newtons) is often converted to tensile strength (pressure, in MPa), since the calculation of tensile strength takes into account the tablet dimensions. The radial (or diametral) tensile strength is calculated according to the following formula:
number
[0048] <Debinding> As described herein, the green tablets are compressed but not debound or sintered. The shaped catalysts are debound and sintered prior to being utilized in catalytic reactions (e.g., oxidative dehydrogenation).
[0049] Debound tablets are those that have been through a debinding process to remove the organic binders before proceeding to the final sintering step. In some embodiments, the debinding process includes a heat treatment step. The heat treatment is carried out slowly during thermal debinding. The green tablets are heated under air to burn off the organic additives. During the debinding process, the combustion produces water and carbon dioxide gas. Therefore, the debinding process is carefully controlled to prevent the buildup of high pressure gases within the tablets.
[0050] Debinding removes the organic binder and plasticizer in the green tablet. Therefore, the maximum temperature of the debinding step is determined based on the organic binder and / or plasticizer in the green tablet. For example, pure polyvinyl alcohol (PVA) decomposes in the range of about 200°C to about 300°C depending on the molecular weight distribution of PVA. In another example, pure polyethylene glycol decomposes in the range of about 150°C to about 250°C depending on the molecular weight distribution of PEG. Therefore, when PEG is used as a binder in the molded catalyst formulation, the minimum temperature of the debinding temperature should be about 250°C.
[0051] In some embodiments, the heat treatment is carried out under an air atmosphere to promote the combustion of the binder (e.g., polyvinyl alcohol). In some embodiments, the ramp rate of the heat treatment step is 1-2°C / min or less to avoid cracking or bursting of the tablets due to carbon dioxide, steam, and other gases released during the heat treatment step. The maximum debinding temperature applied in the debinding process described herein is 550°C-600°C. However, the debinding temperature herein is less than 400°C to avoid oxidation of the catalyst. In the case of the MoVTeTaOx molded catalysts (molded catalysts 1.2-1.7) listed in Table 1, the debinding temperature was 400°C and the ramp rate was 1°C / min. The reason why the debinding temperature was not allowed to exceed 400°C is that a high temperature in an air atmosphere may lead to deactivation of the catalyst. Debinding was carried out in a catalyst calciner.
[0052] <Sintering> After debinding, the tablets undergo a sintering process to increase mechanical strength and become a ceramic final product. Ceramics are any of a variety of hard, brittle, heat- and corrosion-resistant materials made by molding inorganic non-metallic materials such as clay and firing them at high temperatures. The sintering process also forms bridges / bonds between particles, causing them to cohere into a dense solid with increased mechanical strength. Sintering is a kinetic phenomenon between particles that occurs naturally given sufficient time. However, high temperatures can significantly accelerate sintering, reducing sintering times to a few hours. For the tablets described herein, heat treatment is performed under an inert atmosphere during thermal sintering to avoid oxidation of the catalyst. Sintering is typically performed at a higher temperature than debinding, and the heating rate can be increased, for example up to 5° C. / min, since no or very little additional gaseous products are released from the compressed tablets at this stage. In some embodiments, the maximum temperature applied during the sintering process is 600° C. The sintering process results in the final ceramic shaped catalyst without the binder. Sintering allows for both densification and grain growth to be controlled. Densification reduces the porosity of the sample, thereby increasing its density and strength. Grain growth is the process by which grain boundaries move and the average grain size increases. Mechanical strength properties benefit from both high relative density and small grain size. Therefore, when sintering tablets, it is desirable to use high heating rates to prevent large grain sizes. Although little gaseous products are lost during the sintering process, water can escape from the molded catalyst in the form of steam. The amount of water lost can be determined by the loss on ignition test (LOI), an ASTM test described in UOP954-11.
[0053] For the MoVTeTaOx catalysts listed in Table 1, the applied sintering temperature was 600 °C with a heating rate of 1.6 °C / min. The MoVTeTaOx shaped catalysts listed in Table 1 were sintered at a heating rate of 1.6 °C / min, but faster heating rates are also suitable. However, a faster heating rate may weaken the final material due to thermal stresses and rapid moisture release within each particle, which may lead to particle cracking and reduced mechanical integrity. The MoVTeTaOx and MoVTeNbOx catalysts in Table 1 were sintered in a catalyst calciner. Sintering was performed under nitrogen flow because, as described herein, temperatures above 400 °C in air may lead to catalyst deactivation.
[0054] FIG. 3 shows a flow diagram 300 of an exemplary process 300 for debinding and sintering a catalyst. A green body tablet 302 containing an organic binder agent 301 is debound at 400° C. in air in step 304. Carbon dioxide (CO2) gas 305 is released from the green body to obtain a debound body 306. The debound body is then sintered at 600° C. under an inert gas in step 308. In some embodiments, the inert gas is nitrogen gas. Sintering results in a shaped catalyst 310 with increased mechanical strength. Surprisingly, the shaped catalysts described herein exhibit high mechanical strength despite the lack of a binder.
[0055] The shaped catalysts described herein were tested for their ability to catalyze the oxidative dehydrogenation of ethane using a microreactor unit (MRU). The MRU comprises a stainless steel SWAGELOK® tubing reactor tube with an outer diameter of 0.5 inches (1.27 cm), an inner diameter of about 0.4 inches (1.02 cm), and a length of about 13.4 to 15 inches (34.0 to 38.1 cm). The MRU experimental temperature is measured using a 6-point WIKA Instruments Ltd. K-type thermocouple with an outer diameter of 0.125 inches (0.318 cm) inserted into the reactor. The 6-point thermocouple is used to measure and control the temperature within the catalyst bed. A room temperature stainless steel condenser is placed after the reactor to collect the water / acetic acid condensate. If product gas analysis is required, the gas product stream is either vented or directed to an Agilent 8890 "hot gas" gas chromatograph (HGGC). Due to size restrictions during MRU testing, the catalyst pellets were gently crushed into granules using a mortar and pestle. The resulting granules were sieved to collect particle size distributions from 425 μm to 1000 μm and loaded for testing in the MRU. In some embodiments, molded tablets can be used as catalysts without granulation. Depending on whether the molded catalyst contains a support or not, two loading methods were adopted, and the loading time was 5.46 h. -1 A constant weight hourly space velocity (WHSV) was maintained.
[0056] For the shaped catalyst without support (i.e., shaped catalyst 1.2), 2.00 g of catalyst sieved from crushed compacted catalyst with particle sizes between 425 μm and 1000 μm was physically mixed with quartz sand (50-70 mesh) such that the total catalyst bed volume of the mixture was 6 mL. The catalyst bed was loaded into the reactor and connected to the MRU equipment and then tested as described herein.
[0057] For supported shaped catalysts, 4.00-5.00 g of compressed catalyst material with particle sizes between 425 μm and 1000 μm was physically mixed with quartz sand such that the total catalyst bed volume of the mixture was 6 mL. All catalyst materials were prepared with approximately 40 wt% catalytically active phase, so the weight loading of catalyst in the MRU test equipment ranged from 1.60-2.00 g.
[0058] For both supported and unsupported catalysts, the catalyst bed was loaded in the central zone of the reactor (between thermocouple points 2 and 5) and the remaining volume of the reactor was filled with quartz sand. The reactor loading was then secured with glass wool at both the top and bottom of the reactor. The quartz sand added to bring the catalyst bed volume to 6 mL was done to ensure that the catalyst volume adequately covered the thermocouple area between points 2 and 5. When the catalyst was supported, less sand was required to form the 6 mL bed volume due to the increased bed volume provided by the support.
[0059] In the MRU test, a premixed feed gas composition was achieved by an upstream gas mixing device equipped with a calibrated mass flow controller. This premixed feed gas composition was fed to the reactor. The premixed feed gas entering the reactor was 20 mol% ethane, 10 mol% oxygen, and 70 mol% nitrogen (the molar ratio of ethane to oxygen was 1 / 0.5), and the reactor outlet was pressurized to 20 psig (0.14 MPa) using a back pressure regulator. Furthermore, the flow rate of the premixed feed gas was adjusted by a calibrated mass flow controller to obtain a constant weight hourly space velocity (WHSV) based on the weight of the catalytic active phase in the entire catalyst bed.
[0060] The flow rate of the premixed feed gas was controlled at 152–157 standard cubic centimeters (sccm) depending on the weight load for 5.46 h. -1 Constant WHSV5.46h -1was achieved. Gas hourly space velocity (GHSV) was calculated based on the measured volume of compacted particles (before mixing with quartz sand) and varied depending on the bulk density of each catalyst or catalyst material. WHSV is defined as the mass flow rate of the feed gas to the reactor divided by the weight of catalyst in the catalyst bed, and GHSV is defined as the volumetric flow rate of the reactor feed gas divided by the volume of the catalyst bed. For GHSV values of supported catalysts, the catalyst bed includes the diluent (including the support volume). It is also possible to calculate GHSV values for the catalyst only, where the total volume of the measured catalyst material is multiplied by the wt% of catalyst to calculate the catalyst volume. Here, the GHSV value is provided as the total volume of both catalyst and catalyst material. This differs from the reporting method applied to WHSV, which is only the catalyst weight and does not include the support weight. Thus, supported and unsupported catalysts have similar WHSVs but different GHSVs. For supported catalysts, the reported catalyst-only GHSV is calculated as the volume of catalyst by multiplying the total volume of catalyst material measured by the wt% of catalyst.
[0061] In the MRU experiment, the ethane conversion temperature in mol% was 5.46 h -1 , Gas hourly space velocity (GHSV) is 3000~7000h -1 The conversion of the ethane feed gas (C) was calculated as the change in volumetric flow rate of ethane in the product compared to the feed ethane mass flow rate using the following equation:
number
[0062] Additionally, the gas exiting the reactor was analyzed by GC to determine the selectivity of the catalyst or catalyst material to ethylene (i.e., the percentage of ethane on a molar basis that forms ethylene). The selectivity to ethylene (S エチレン ) was determined using the following formula:
number
[0063] 4 is a flow chart of an exemplary method 400 for the oxidative dehydrogenation of ethane. At 402, a feed gas containing ethane, oxygen, and nitrogen is flowed into a microreactor unit. At 404, the feed gas is pressurized to 20 psig (0.14 MPa). In some embodiments, the feed gas can be pressurized to 2-80 psig. At 406, the feed gas is contacted with a shaped catalyst described herein. At 408, the feed gas is heated to 450° C.-470° C. At 410, ethylene gas is recovered.
[0064] The catalyst was analyzed in MRU short-term runs and MRU long-term runs. The MRU short-term runs were conducted the day before the long-term runs to determine ethane conversion conditions of approximately 50 mol%. In the MRU short-term runs, the catalyst was tested in the MRU at several temperature conditions from 340 to 480 °C while keeping the feed composition and weight hourly space velocity (WHSV) constant. At each temperature condition, gas samples were passed through a gas chromatogram (GC) to obtain the composition of the gas products. The conversion was calculated as the percentage of atomic carbon in the ethane product, as shown in Eq. 3, which is the percentage of atomic carbon in all carbon products, including ethane, ethylene, carbon dioxide, and carbon monoxide. The ethylene selectivity was calculated as the percentage of ethane to ethylene at each temperature. The amount of acetic acid produced was small enough that the amount of acetic acid could be excluded from Eqs. 3 and 4 when calculating the conversion and selectivity.
[0065] Once the 50 mol% ethane conversion temperature was determined in the short run, a long-term MRU experiment was performed at this temperature. The MRU was ramped up to the determined temperature and waited until the process stabilized (usually about 30 minutes). After the process stabilized, a GC injection was performed to confirm that the ethane conversion was close to 50 mol% (±2%). If the conditions were correct to achieve 50 mol% ethane conversion, the MRU long-term run was initiated, otherwise the conditions (temperature) were adjusted to bring the conversion closer to the target conversion. Once the target conditions of stable conversion and selectivity were met, the experiment timer for the long-term run was started.
[0066] Long-term MRU runs provide information on the stability of catalyst performance with increasing time, which for heterogeneous catalysts is often referred to as "times on stream" (TOS). Ideally, the longer the TOS period, the more stable the catalyst conversion and selectivity should be and remain relatively unchanged throughout the duration of the experiment. It is not uncommon for heterogeneous catalysts to be more active (higher conversion) within the first 24-72 hours, after which the conversion stabilizes. However, the important trend to observe in long-term runs is that at some point in the experiment, the catalyst conversion trend moves in a direction that does not change with increasing experimental time (flat or nearly flat line trend in an x vs. y plot). Equally, or perhaps even more importantly, ethylene selectivity should also show a stable trend that does not decrease with increasing TOS. The MRU long-term validation test will be conducted for 42 days or 1008 hours of on-stream time.
[0067] Catalysts may also exhibit deactivation over time in MRU experiments or other catalytic processes. Advantageously, the shaped catalysts described herein have a very subtle tendency to deactivate, which only becomes apparent over extended experiments (e.g., 300 hours or more). The rate of deactivation can be expressed as absolute mol% ethane conversion / hour. Thus, the catalysts described herein are stable over extended experiments and can be reused multiple times.
[0068] [Table 1]
[0069] The reagents for the experiments described herein were purchased from the manufacturer and used as is without further purification. The following chemicals were purchased from Sigma Aldrich: fumed synthetic amorphous silica (product number S5130), natural graphite (product number 1002969522), MOWIOL® 4-88 31,000 MW polyvinyl alcohol (product number 81381), 1000 MW polyethylene glycol (product number 81189), magnesium stearate (product number 415057). The following chemicals were obtained from Saint-Gobain: alpha-alumina (DENSTONE® 99), silica XS 69025 catalyst support tablets (sample number 2001910060), aluminum silicate SA 3X32 catalyst support tablets (sample number 2002920068), and gamma alumina SA 6X73 catalyst support tablets (sample number 2007910008). The alpha-alumina (DENSTONE® 99) was prepared for use by dry ball milling using a RETSCH® PM100. Dry ball milling was performed using 3 mm zirconia balls and 500 mL zirconia grinding jars. Precipitated synthetic amorphous silica was obtained from PQ Corporation (product identifier PQ BRITESORB® C935).
[0070] In some embodiments, the MoVTeTaOx catalytic active phase is prepared by dissolving (NH4)6Mo7O in 27 L of distilled water in a 50 L glass vessel heated to a temperature of 60° C. 24 Prepared by dissolving 4H2O(s) salt (2372.0 g; 1.9 mol) and rinsing with 3 L of distilled water (volume: 1 L for powder lifting + 2 L after transferring solution to SS reactor). (NH4)6Mo7O 24The (aq) solution was clear and colorless and had a measured pH of 5.04 at 55.0 °C. Te(OH)6(s) salt (514 g; 2.25 mol) was dissolved in 2 L of distilled water in a 20 L PFA container heated to 55 °C, with an additional 3 L of distilled water used for rinsing (1 L + 2 L portions). The Te(OH)6(aq) solution was clear and colorless. The Te(OH)6(aq) solution was dissolved in 2 L of (NH4)6Mo7O at 60 °C. 24 (aq) solution in one go. There was no visible change in the solution upon addition, but the pH dropped to 3.20 at 53.0°C. (NH4)6Mo6TeO 24 After the solution reached 55°C, the pH of the solution was adjusted to pH 5.2 using 104.7g of 28wt% NH4OH(aq) dropwise. The final pH was measured to be 5.23 at 56.9°C. The temperature of the solution was raised to 78°C and it took 1h 25min for the solution to reach 78°C. The solution was stirred at 78°C for 1h. The pH was remeasured at 78°C, which was 4.91, before the solution was cooled to 60°C. The 60°C solution was pumped into a 100L glass-lined SS reactor vessel preheated to a surface temperature of 60°C. VOSO4·3.36H2O salt (1989g; 8.902mol) was dissolved in 8L of distilled water in a 20L perfluoroalkoxy (PFA) vessel heated to a temperature of 55°C and an additional 4L of water was used to rinse (2L+2L). The VOSO4(aq) solution was clear and bright blue in color. After homogenization, the VOSO4(aq) solution at 55 °C was transferred to the 100 L SS reactor vessel with a controlled pump rate of 367 mL / min and stirred at 22 rpm while adding (NH4)6Mo6TeO 24 (aq) solution was mixed.
[0071] 1.3 L of tantalum reagent (192 g Ta2O5 and 122 g oxalate per L of aqueous solution) was diluted with 2 L of distilled water in a 20 L PFA container at room temperature. An additional 3 L of distilled water was used to rinse (1 L + 2 L). The tantalum oxalate solution was pumped into the MoTeV solution in the SS reactor at a rate of 183 mL / min and the reactor contents were mixed at 22 rpm. After the addition was complete, the reaction mixture was stirred in air at 60°C for 1 hour. The total volume of water used in the reaction was 53 L, including the uptake. The reactor was sealed and the headspace was purged four times with alternating 10 psig nitrogen gas and vacuum. The reactor was left sealed with a nitrogen headspace of 20 psig. The back pressure regulator was set at approximately 140 psig and the heat controller was set at 165°C. The reactor skin temperature limit setting was 195°C. After about 20 hours, the slurry in the reactor reached 160°C. The reaction time was started from that point. The reaction time was 48 hours. The pressure in the reactor reached a maximum of 103 psig. After 48 hours of reaction, the reactor heater was turned off and the slurry was cooled to 68°C with continued stirring. The deep purple slurry was transferred to a filter unit where the solids were filtered. The catalyst cake formed on the filter was washed with a total of 200 L of distilled water (in portions of 40 L and 20 L).
[0072] This device, attached to the reactor head, was a tube-in-tube exchanger (condenser) with cooling water circulating through the outer tube at approximately 25°C (closed system, controlled by a cooling bath) and the inner tube connected to the reactor (process) to allow the venting of excess gas pressure via a back pressure regulator.
[0073] The resulting solid cake was removed from the filter unit and transferred to an oven where it was dried in air at 90° C. for 4 days. The dried cake weighed 1937 g, giving a yield of 57%. The cake was crushed to a powder using a RETSCH jaw crusher BB50 grinder.
[0074] The green cakes were loaded into two quartz boats and the catalyst was air-conditioned in an oven at 250°C for 6 hours. After air conditioning, the boats were transferred to the quartz tube of a catalyst calcination furnace and purged with bulk nitrogen at a flow rate of 1000 sccm overnight. Two hours before starting the furnace, the bulk inlet nitrogen purge (<10 ppm oxygen) was redirected through an oxygen trap (LabClear™ Oxiclear™ Gas Purifier) and the quartz tube was purged with purified nitrogen (<1 ppm oxygen). The catalyst was calcined at 600°C under purified nitrogen for 4 hours. The calcination was ramped at a heating rate of 1.6°C / min. After cooling to room temperature, the calcination yield was determined to be 93.5 wt% recovery.
[0075] The final calcined MoVTeTaOx is referred to herein as Catalyst 1. It will be understood that other procedures may be used to form Catalyst 1. Additionally, any number of ratios of metals may be used.
[0076] In some embodiments, the MoVTeNbOx catalyst active phase was prepared by weighing 11.37 g of Nb2O5·H2O and approximately 127 mL of deionized water into a 250 mL RBF. 19.09 g of oxalic acid (H2C2O4) was added and stirred at 65 °C for 24 hours to obtain a cloudy solution of niobium oxalate.
[0077] 84.28g of (NH4)6Mo7O 24 4H2O and approximately 200 mL of deionized water were weighed into a 500 mL round bottom flask (RBF) and stirred to dissolve the powder. 18.27 g of telluric acid and approximately 50 mL of deionized water were weighed into a 100 mL beaker and the mixture was stirred at approximately 50 °C to dissolve the powder. The telluric acid solution was dissolved in water at room temperature to obtain (NH4)6Mo7O 24 4H2O solution was added dropwise. The Mo / Te solution was heated to approximately 80°C using an oil bath. 28.0 mL of NH4OH solution was added dropwise to the Mo / Te solution and the pH was adjusted to 7.5 at 80°C. The contents of the flask were left stirring at 80°C for 2 h. 28.0 mL of 5 M H2SO4 solution was added dropwise to the flask and the pH was adjusted to 4.99. The contents of the flask were stirred at 80° C. for approximately 2 hours.
[0078] 70.04 g of VOSO4·3.41H2O and approximately 150 mL of deionized water were weighed into a 250 mL beaker and the mixture was stirred to dissolve the powder. In a 2 L RBF, the VOSO4 solution was added dropwise using an addition funnel to the Mo / Te solution at 70 °C and stirred for approximately 30 min to form an opaque purple solution.
[0079] The previously prepared niobium oxalate solution was slowly added to the 70 °C purple solution using a dropping funnel and stirred for about 30 min to form a greenish slurry with a purple film on the walls of the RBF. The green slurry was transferred to a 2 L glass liner equipped with a large magnetic stir bar.
[0080] The glass liner was placed inside the steel body of the autoclave and the cover was sealed to the steel body. The autoclave was slowly filled with nitrogen and then evacuated 10 times to remove the headspace air. The autoclave was left overnight (approximately 10-16 hours) at approximately 15 psig of nitrogen and stirred at approximately 200 rpm. The nitrogen headspace pressure was released through a bubbler to purge the air from the lines.
[0081] After stirring overnight, the autoclave back pressure regulator was set to 160 psig, the temperature controller was increased to 170° C., and the outline condenser water bath was set to 25° C. The temperature profile was monitored. The reaction was stirred at 200 rpm for an additional 17 hours at 165° C., for a total of approximately 24 hours.
[0082] The heat was turned off, the top valve was closed, the insulation was removed, and the reactor was allowed to cool overnight with stirring at 200 rpm. The pressure in the reactor was released by opening the top valve.
[0083] The reactor was disassembled and the glass liner was removed. The contents were filtered through a Büchner funnel equipped with four sheets of WHATMAN® #4 filter paper (available from Sigma Aldrich) using an aspirator. The resulting filter cake was washed with deionized water until the filtrate was clear. The filter cake was dried in a 90° C. oven over the weekend (about 48 to about 60 hours) and cooled to room temperature.
[0084] A portion of the dried filter cake was manually crushed using a mortar and pestle. The crushed catalyst was loaded into a boat and calcined at 600 °C under nitrogen flow.
[0085] The final calcined MoVTeNbOx is referred to herein as Catalyst 2. It will be appreciated that other procedures may be used to form Catalyst 2. Additionally, any number of ratios of metals may be used.
[0086] Distilled water was prepared in-house using a Corning Mega Pure™ 12A System ACS as the distillation apparatus. EXAMPLES
[0087] [Example 1: Granule particle size distribution] The effect of the particle size distribution of the granules on the strength of the green body tablets was investigated. Molded catalyst formulations containing the active catalyst phase, support, binder, and optionally lubricant were prepared in a tablet press as described herein. Table 2 shows the particle size distribution of the granules used to investigate the effect of particle size on the crush strength of the automated pressed tablets of molded catalyst 1.4 (green body). The tablets in Table 2 were produced using a CPR-6 automated press. First, 0.3616 g of polyethylene glycol (PEG) and 1.4437 g of polyvinyl chloride (PVA) were combined in a 1000 mL beaker. Next, 80 mL of distilled water was added to the beaker. The beaker was placed in a 65° C. water bath on a stirring hot plate and the chemicals were dissolved while stirring. After the chemicals were dissolved, 24.0622 g of catalyst 1 and 36.16 g of fumed silica were combined in a separate container and then added to the 1000 mL beaker containing the dissolved PVA / PEG. An additional 160 mL of distilled water was added to form a flowable slurry. The water bath setting was increased to 95 °C. The slurry was stirred with an overhead stirrer until most of the water had evaporated and the mixture formed a thick paste. The beaker containing the paste was placed in a 105 °C oven overnight to dry completely.
[0088] Next, the blended catalyst was granulated. Granulation was carried out by producing briquettes, crushing the briquettes, sieving the formed granules, and collecting the granules having dimensions within the size range (> 105 μm and < 710 μm). Before briquetting, the blended solid catalyst was first powdered using a mortar and pestle. Approximately 7 g of the powder was loaded into a 4 cm diameter die set and pressed at 12 metric tons for 60 seconds using a CARVER manual press to produce briquettes. The briquettes were then crushed using a mortar and pestle to obtain granules. These granules were sieved using sieves of sizes 105 μm, 250 μm, 500 μm, and 710 μm. The granules collected on the sieve from 105 μm to 500 μm were collected for further experiments (size range > 105 μm and < 710 μm). The granulation process was repeated several times until a satisfactory amount of granules was obtained. Table 2 shows the particle size distribution used in this experiment. Next, the granules were tableted into 3 mm tablets. The granulated catalyst sample was mixed with 2 wt% graphite as a lubricant and tableted using a CPR-6 automatic single punch tablet press.
[0089] The settings of the tablet press for all the above samples were an upper die pressure of 8, a lower die setting of 2, and a tableting speed of 4. The axial crushing strength was measured by slowly applying a load in the axial direction of the cylindrical tablet, i.e., to the flat surface, to a tablet sandwiched between two flat plates. The largest force recorded when the tablet broke was recorded as the crushing strength. The apparatus used for measuring the crushing strength included a CHATILLON® TCM201 drive and a MECMESIN® AFG2500N force gauge attached to the drive.
[0090] Comparing the values of the crushing strength of the shaped catalysts 1.4, 1.4-E1, 1.4-E2, and 1.4-E3, it was found that E2 with a particle size distribution (x) of 250 μm < x < 500 μm achieved the highest crushing strength.
[0091]
Table 2
[0092] [Example 2: Tablet processability data for molded catalyst 1.5 tablets] In addition to the axial strength measurements of the 3 mm molded catalyst 1.4 tablets, the radial crush strength of the 6 mm molded catalyst 1.5 (green body, GB) tablets was examined. The tablets were prepared on an automated press. The molded catalyst 1.5 (GB) tablets were prepared by combining 0.4009 g of polyethylene glycol (PEG) and 1.6159 g of polyvinyl chloride (PVA) in a 500 mL beaker. Then, 60 mL of distilled water was added to the beaker. The beaker was placed in a 65 °C water bath on a stirring hot plate and the chemicals were dissolved while stirring. After the chemicals were dissolved, 16.0457 g of catalyst active phase catalyst 1 and 24.0425 g of fumed silica were weighed out and combined in a separate container. The catalyst / silica mixture was then added to the 500 mL beaker containing the dissolved PVA / PEG. An additional 150 mL of distilled water was added to form a flowable slurry. The water bath was then increased to 95 °C. The slurry was stirred using an overhead stirrer until most of the water had evaporated and the mixture became a thick paste. The beaker containing the paste was placed in a 105° C. oven overnight to dry thoroughly.
[0093] The blended solid catalyst was then powdered in a mortar and pestle. Approximately 7 g of powder was loaded into a die set of 4 cm diameter and pressed in a CARVER manual press at 12 metric tons for 60 seconds to produce briquettes. The briquettes were then crushed using a mortar and pestle to obtain granules. The granules were sieved using sieves of 250 μm and 500 μm size. The granules collected on the 250 μm sieve were collected for further experiments (size range >250 μm and <500 μm). The granulation process was repeated several times until a satisfactory weight of granules was obtained. The granules were used for tableting.
[0094] The granulated catalyst was tableted using a CPR-6 automatic single punch tablet press. The machine settings were upper die setting 8, lower die setting 2, and the tableting speed was varied between 1 and 3. Tabletting produced shaped catalyst 1.5 (green body, GB).
[0095] FIG. 5 shows the tabletability profile of Molded Catalyst 1.5 green body tablets (Molded Catalyst 1.5GB). The diameter of the tablets tested was 6 mm. The radial crush strength (MPa) was tested at various compression pressures along the diameter of the cylindrical tablet by slowly applying a load to the tablet sandwiched between two flat plates. The highest force recorded at which the tablet breaks is recorded as the radial crush strength. The apparatus used to measure the crush strength included a CHATILLON® TCM201 drive and a MECMESIN® AFG2500N force gauge attached to the drive. The radial crush strength was converted to a tensile strength value as described herein.
[0096] As shown in Figure 5, the radial tensile strength of the molded catalyst 1.5GB tablets increased with increasing compression pressure. The increase in radial tensile strength as the compression pressure of the catalyst tablets 1.5GB increased indicates that these tablets are well suited for tablet compression. In addition, these tablets have radial tensile strengths of over 2 MPa, further indicating their suitability as catalysts.
[0097] [Example 3: Tablet processability data for molded catalyst 1.7 tablets] The preparation of shaped catalyst 1.7 tablets was done by combining 0.8079 g of polyethylene glycol (PEG) and 1.1960 g of polyvinyl chloride (PVA) in a 1000 mL beaker. Then, 100 mL of distilled water was added to the beaker. The beaker was placed in a 65 °C water bath on a stirring hot plate and the chemicals were dissolved while stirring. After the chemicals were dissolved, 16.0320 g of catalyst 1 and 24.05 g of fumed silica were combined in a separate container and then added to the 1000 mL beaker containing the dissolved PVA / PEG. An additional 150 mL of DI water was added to form a flowable slurry. The water bath was increased to 95 °C. The slurry was stirred with an overhead stirrer until most of the water had evaporated and the mixture formed a thick paste. The beaker containing the paste was placed in a 105 °C oven overnight to dry completely.
[0098] The combined solid catalyst was then pulverized in a mortar and pestle. Approximately 7 g of powder was loaded into a die set of 4 cm diameter and pressed in a CARVER manual press at 12 metric tons for 60 seconds to produce briquettes. The briquettes were then crushed using a mortar and pestle to obtain granules. The granules were sieved using sieves of 250 μm and 500 μm size. The granules collected on the 250 μm sieve were collected for further experiments (size range >250 μm and <500 μm). The granulation process was repeated several times until sufficient granules were obtained for tableting.
[0099] The granulated catalyst was tableted using a CPR-6 automatic single punch tablet press. The machine settings were upper die setting 8, lower die setting 2, and the tableting speed was varied between 1 and 3. Tabletting produced shaped catalyst 1.7 (green body, GB).
[0100] The radial crush strength of molded catalyst 1.7GB tablets was tested at various compression pressures along the diameter of the cylindrical tablet by slowly applying a load to the tablet sandwiched between two flat plates. The highest force recorded at which the tablet breaks is recorded as the radial crush strength. The equipment used to measure the crush strength included a CHATILLON TCM201 drive and a MECMESIN AFG2500N force gauge attached to the drive. The radial crush strength is converted to a tensile strength value as described herein.
[0101] Figure 6 shows the tabletability profile, i.e., radial tensile strength (MPa) as a function of compression pressure (MPa), of the molded catalyst 1.7GB tablets. As shown in Figure 6, the molded catalyst 1.7GB tablets exhibited an increase in radial tensile strength with increasing compression pressure. The increase in radial tensile strength with increasing compression pressure of catalyst tablets 1.7GB indicates that these tablets are well suited for tablet compression. Furthermore, these tablets have a radial tensile strength of over 2 MPa, further indicating their suitability as catalysts.
[0102] As shown in Examples 2 and 3, the crushing strength of the molded catalyst tablet (1.5GB) with a binder content of 5% by weight was about 63% higher than that of the molded catalyst tablet (1.4-E2-GB) with a binder content of about 3% by weight. Thus, the molded catalyst green tablets prepared with a high binder content had crushing strength more than twice as high as the molded catalyst green tablets prepared with a low binder content. This was a surprising result.
[0103] [Example 4: Tabletability profile of Comparative Examples 2.1 and 2.2] Comparative examples were analyzed to evaluate the tabletability profile of the catalyst formulations. These comparative examples contained support and binder components, but no catalyst. Two comparative formulations contained alpha alumina (shaped catalyst 2.1) and fumed silica (shaped catalyst 2.2) support materials. Comparative shaped catalysts 2.1 and 2.2 were formulated as shown in Table 1.
[0104] For comparative example tablets of molded catalyst 2.1, 0.8143 g of polyethylene glycol (PEG) and 1.2111 g of polyvinyl chloride (PVA) were combined in a 1000 mL beaker. 50 mL of distilled water was then added to the beaker. The beaker was placed in a 65°C water bath on a stirring hot plate and stirred to dissolve the chemicals. After the chemicals were dissolved, 39.9 g of fumed silica was added to the 1000 mL beaker containing the dissolved PVA / PEG. An additional 120 mL of distilled water was added to form a flowable slurry. The water bath was increased to 95°C. The slurry was stirred with an overhead stirrer until most of the water had evaporated and the mixture formed a thick paste. The beaker containing the paste was placed in a 105°C oven overnight to dry completely.
[0105] The resulting dried "cake" was ground into granules using a mortar and pestle, but was not compressed into briquettes as in the other samples. The granules were sieved using 250 μm and 500 μm size sieves. The granules collected in the 250 μm size sieve were collected for further experiments (size range >250 μm and <500 μm). The granulation process was repeated several times until a satisfactory weight of granules was obtained. The granules were used for tableting. The granulated catalyst was tableted using a CPR-6 automatic single punch tablet press. The sample was manually loaded into the press die.
[0106] For comparative example tablets of molded catalyst 2.2, 0.7976 g of polyethylene glycol (PEG) and 1.2018 g of polyvinyl chloride (PVA) were combined in a 350 mL beaker. 50 mL of distilled water was then added to the beaker. The beaker was placed in a 65°C water bath on a stirring hot plate and the chemicals were dissolved with stirring. After the chemicals were dissolved, 40.1682 g of dry ball milled DENSTONE 99 alpha alumina was added to the 350 mL beaker containing the dissolved PVA / PEG. A flowable slurry was formed. The temperature of the water bath was increased to 95°C. The slurry was stirred with an overhead stirrer until most of the water had evaporated and the mixture formed a thick paste. The beaker containing the paste was placed in a 105°C oven overnight to dry completely.
[0107] After drying overnight, the paste becomes a dry "cake" i.e. an agglomerated solid powder that can be crushed and molded. The resulting solid powder was crushed into granules with a mortar and pestle, but was not compressed into briquettes as in the other samples. The granules were sieved using sieves of 250 μm and 500 μm size. The granules collected on the sieve of 250 μm size were collected for further experiments (size range >250 μm and <500 μm). The granulation process was repeated several times until sufficient amount of granules was obtained for tableting.
[0108] The granulated catalyst was tableted using a CPR-6 automatic press, with the sample manually loaded into the press die.
[0109] The radial crush strength of comparative molded catalyst 2.1GB and 2.2GB tablets was tested at various compression pressures along the diameter of the cylindrical tablet by slowly applying a load to the tablet sandwiched between two flat plates. The highest force recorded at which the tablet breaks is recorded as the radial crush strength. The equipment used to measure the crush strength included a CHATILLON TCM201 drive and a MECMESIN AFG2500N force gauge attached to the drive. The radial crush strength was converted to a tensile strength value as described herein.
[0110] FIG. 7 shows the tabletability profiles of molded catalyst 2.1GB (comparative tablet) and molded catalyst 2.2GB (comparative tablet) (circles). The tested tablets had a diameter of 6 mm. As shown in FIG. 7, the molded catalyst 2.2GB comparative tablet did not increase in radial tensile strength with increasing compression pressure, suggesting that fumed silica alone is not an ideal tablet compression material. Rather, the fumed silica support and catalyst active phase act synergistically to improve the strength and tabletability of the molded catalyst tablets. This was another surprising result.
[0111] The comparative molded catalyst 2.1GB tablets exhibited increased radial tensile strength with increasing compression pressure, however the comparative molded catalyst 2.1GB tablets contain an alpha alumina support phase.
[0112] While not wishing to be bound by theory, it has been suggested that when the MoVTeTaOx catalytically active phase is combined with fumed silica, the new material mixture behaves like an ideal compressible material, whereas fumed silica formulations without the catalyst do not exhibit these properties. Furthermore, combining fumed silica with the MoVTeTaOx catalytically active phase produces a material that is better at compressing wells than existing supports such as alpha alumina.
[0113] [Example 5: Mechanical strength data] The mechanical strength of the shaped catalysts 1.2-1.8 tablets (as green bodies and sintered bodies) was analyzed. Table 3 shows the granule sizes of the formulations used to make shaped catalysts 1.2-1.8 in this experiment.
[0114] [Table 3]
[0115] <Synthesis of molded catalyst 1.2> The synthesis of shaped catalyst 1.2 tablets was carried out by combining 0.0824 g of polyethylene glycol (PEG) and 0.3473 g of polyvinyl chloride (PVA) in a 100 mL beaker. Then, 10 mL of distilled water was added to the beaker. The beaker was placed in a 65 °C water bath on a stirring hot plate and the chemicals were dissolved while stirring. In a separate 500 mL beaker, 5.7040 g of catalyst active phase catalyst 1 and 8.3985 g of fumed silica were combined. After the PGA / PVA mixture was dissolved, it was combined with the catalyst / silica mixture. The 500 mL beaker with all four chemicals mixed was placed in a water bath set at 95 °C. The slurry was stirred with an overhead stirrer until most of the water had evaporated and the mixture formed a thick paste. The beaker containing the paste was placed in a 105 °C oven overnight to dry completely.
[0116] The compounded solid catalyst was then pulverized in a mortar and pestle. Approximately 7 g of powder was loaded into a die set of 4 cm diameter and pressed in a CARVER manual press at 12 metric tons for 60 seconds to produce briquettes. The briquettes were then crushed using a mortar and pestle. The resulting granules were sieved using sieves of 105 μm, 250 μm, 500 μm, and 710 μm sizes. The granules collected in the 105 μm to 500 μm sieve were collected for further experiments (size range >105 μm and <710 μm). The granulation process was repeated several times until sufficient amount of granules was obtained for tableting.
[0117] For tableting, 2 wt% natural graphite was added to the granules as a lubricant and mixed well. The granulated catalyst was tableted using a CPR-6 automatic single punch tablet press. The machine settings were upper die pressure of 8, lower die setting of 1, and tableting speed of 4. Tabletting produced green body tablets.
[0118] In the sintering experiments, the green tablets were prepared, debound, and sintered. Debinding was performed in a catalytic calcination furnace (CCF). The tablets were loaded into a quartz boat, which was then inserted into the quartz tube of the CCF. The quartz tube was sealed except for the inlet and outlet lines, which were used to flow purified air at 300 sccm into the quartz tube during the process. Purified air is air that has had impurities removed, for example bottled air or zero air. Zero air is air that has had hydrocarbons removed by a catalytic oxidation process, resulting in a total hydrocarbon content of less than 0.1 ppm. The furnace was heated to 400 °C at a rate of 1 °C / min, and held at 400 °C for 1 hour, after which heating was stopped and the furnace was cooled.
[0119] After the furnace was cooled to room temperature, the sintering process was started in the same furnace. The air flow was switched to 300 sccm N2 flow. The molded catalyst was purged with N2 for at least 6 hours at room temperature. After purging, the furnace was heated to 600°C at a rate of 1.6°C / min with continuous N2 flow and held at 600°C for 2 hours, then naturally cooled to room temperature. The resulting molded catalyst tablets were removed for analysis.
[0120] <Synthesis of molded catalyst 1.3> The synthesis of shaped catalyst 1.3 tablets was carried out by combining 0.1236 g of polyethylene glycol and 0.4870 g of polyvinyl chloride in a 400 mL beaker. Then, 50 mL of distilled water was added to the beaker. The beaker was placed in a 65 °C water bath on a stirring hot plate and the chemicals were dissolved while stirring. After the chemicals were dissolved, 8.0356 g of catalyst active phase catalyst 1 and 12.0590 g of fumed silica were mixed and added to the same beaker and combined with the other two chemicals. Further, 40 mL of distilled water was added to form a flowable slurry. The water bath setting was increased to 95 °C. The slurry was stirred with an overhead stirrer until most of the water had evaporated and the mixture became a thick paste. The beaker containing the paste was placed in a 105 °C oven overnight to dry completely.
[0121] The compounded solid catalyst was then granulated using the same procedure used in shaped catalyst 1.2. The resulting granules were tableted. The granulated catalyst was tableted using a CPR-6 automatic press. The machine settings were upper die pressure of 8 and lower die setting of 1. The tableting speeds were both 5. The goal was to obtain two types of tablets, one with low crushing strength and one with high crushing strength, to see if the catalyst tablets have different activities in future experiments. Tabletting resulted in green body tablets.
[0122] In the sintering experiments, green tablets were prepared, debindered, and sintered. Debindering and sintering of shaped catalyst 1.3 were carried out using the same procedure as for shaped catalyst 1.2.
[0123] <Synthesis of molded catalyst 1.4-E2> The synthesis of shaped catalyst 1.4-E2 tablets was carried out using the same procedure as described in Example 1. For the sintering experiments, green tablets were synthesized, debindered and sintered using the same procedure as for shaped catalyst 1.2.
[0124] <Synthesis of molded catalyst 1.5> The synthesis of shaped catalyst 1.5 was carried out using the same procedure as described in Example 2. For the sintering experiments, the green tablets were further debindered and sintered. The debindering and sintering of shaped catalyst 1.5 was carried out using the same procedure as shaped catalyst 1.2.
[0125] <Synthesis of molded catalyst 1.6> The synthesis of shaped catalyst 1.6 was carried out by combining 0.8061 g of polyethylene glycol (PEG) and 1.2062 g of polyvinyl chloride (PVA) in a 1000 mL beaker. Then, 100 mL of distilled water was added to the beaker. The beaker was placed in a 65 °C water bath on a stirring hot plate and the chemicals were dissolved while stirring. After the chemicals were dissolved, 16.0443 g of catalyst active phase catalyst 1 and 24.0130 g of fumed silica were combined in a separate container and then the catalyst / silica mixture was added to the 1000 mL beaker containing the dissolved PVA / PEG. An additional 120 mL of distilled water was added to form a flowable slurry. The water bath setting was increased to 95 °C. The slurry was stirred with an overhead stirrer until most of the water had evaporated and the mixture formed a thick paste. The beaker containing the paste was placed in a 105 °C oven overnight to dry completely.
[0126] The resulting dried "cake" was powdered in a mortar and pestle. Approximately 7 g of powder was loaded into a 4 cm diameter die set and pressed in a CARVER manual press at 12 metric tons for 60 seconds to produce briquettes. The briquettes were then crushed using a mortar and pestle to form granules. The granules were sieved using sieves of 250 μm and 500 μm size. The granules collected on the 250 μm sieve were collected for further experiments (size range >250 μm and <500 μm). The granulation process was repeated several times until a sufficient amount of granules was obtained for tableting.
[0127] The granulated catalyst was tableted using a CPR-6 automatic single punch tablet press with machine settings of upper die setting 8, lower die setting 2, and tableting speeds varied between 1 and 3.
[0128] In the sintered experiments, the green tablets were further debindered and sintered using the same procedure as for shaped catalyst 1.2.
[0129] <Synthesis of molded catalyst 1.7> The synthesis of shaped catalyst 1.7 was carried out using the same procedure as described in Example 3. For the sintering experiments, the green tablets were further debindered and sintered using the same procedure as for shaped catalyst 1.2.
[0130] <Synthesis of molded catalyst 1.8> The synthesis of shaped catalyst 1.8 tablets was carried out by combining 0.8099 g of polyethylene glycol (PEG) and 1.1990 g of polyvinyl chloride (PVA) in a 1000 mL beaker. 50 mL of distilled water was then added to the beaker. The beaker was placed in a 65 °C water bath on a stirring hot plate and stirred to dissolve the chemicals. After the chemicals were dissolved, 16.0320 g of catalyst active phase catalyst 2 and 24.00 g of fumed silica were combined in a separate container and then added to the 1000 mL beaker containing the dissolved PVA / PEG. An additional 200 mL of distilled water was added to form a flowable slurry. The water bath setting was increased to 95 °C. The slurry was stirred with an overhead stirrer until most of the water had evaporated and the mixture formed a thick paste. The beaker containing the paste was placed in a 105 °C oven overnight to dry completely.
[0131] The resulting solid powder was pulverized in a mortar and pestle. Approximately 7 g of powder was loaded into a die set of 4 cm diameter and pressed in a CARVER manual press at 12 metric tons for 60 seconds to produce briquettes. The briquettes were then crushed using a mortar and pestle. The granules were sieved using sieves of 250 μm and 500 μm size. The granules collected on the 250 μm sieve were collected for further experiments (size range >250 μm and <500 μm). The granulation process was repeated several times until sufficient granules were obtained for tableting.
[0132] The granulated catalyst was tableted using a CPR-6 automatic single punch tablet press with machine settings of upper die setting 8, lower die setting 2, and tableting speeds varied between 1 and 3.
[0133] For the sintered experiments, the green tablets were further debindered and sintered using the same procedure as described for shaped catalyst 1.2.
[0134] <Mechanical strength experiment> Two mechanical strength measurements were collected, axial crush strength and radial crush strength, both reported in units of Newtons (N). The axial and radial crush strengths were obtained using the same procedures described in Examples 1-3. The axial crush strengths (units: Newtons, N) of the green and sintered bodies are shown in Table 4. The radial crush strengths of the sintered bodies are shown in Table 5.
[0135] As shown in Table 4, the shaped catalysts described herein have high mechanical strength both as green bodies and as sintered bodies. Tablets containing about 3% binder (shaped catalysts 1.3, 1.4, and 1.6) showed increased mechanical strength after sintering, regardless of whether the binder was 80 / 20 PVA / PEG or 60 / 40 PVA / PEG. For tablets containing about 5% binder (shaped catalysts 1.5, 1.7, and 1.8), the tablets with a PVA / PEG ratio of 60 / 40 showed increased mechanical strength after sintering.
[0136] Furthermore, as shown in Tables 4 and 5, the shaped catalysts containing the MoVTeNbOx active phase exhibited high mechanical strength both as green bodies and as sintered bodies, which is a surprising result and indicates a synergistic effect between the MoVTeNbOx active phase and the fumed silica support.
[0137] The tabletability profile indicates that the formulation is suitable for processing on tablet compression equipment.
[0138] [Table 4]
[0139] [Table 5]
[0140] [Example 6: Apparent Density Data] The apparent density of the catalyst tablets described herein shows the effect of the weight percentage of binder on catalyst densification and how increasing density relates to increasing crush strength. Table 6 shows the tablet size, weight, and apparent density data for 3 mm sintered catalyst tablets 1.4-E1-SB, 1.4-E2-SB, 1.4-E3-SB, and 1.5SB-1.8SB. The sintered tablets were prepared as described in Examples 1 to 5. For each analysis, five tablets were analyzed.
[0141] As shown herein, compact catalyst tablet 1.5SB has a higher density than compact catalyst tablet 1.6SB, indicating that the 60 / 40 PVA / PEG binder combination was not as strong as the 80 / 20 PVA / PEG blend when loaded at 3 wt%. The more important factor is the increase in binder content from 3 wt% to 5 wt%. Compact catalyst tablet 1.5 and compact catalyst tablet 1.7, both at 5 wt% binder, have different PVA / PEG ratios but produce similar densities.
[0142] Molded catalyst tablet 1.8 has a modified catalytic phase (MoVTeNbOx vs. MoVTeTaOx) but the same fumed silica / binder formulation as molded catalyst tablet 1.7. This indicates that the catalytic active phase is responsible for the compressibility / mechanical strength / density synergy of the overall mixture. Furthermore, density and crushing strength (i.e. mechanical strength) are directly related from the given data. As shown herein, the higher the density, the higher the crushing strength.
[0143] [Table 6]
[0144] [Example 7: MRU data, comparison example: shape of MoVTeTaOx catalyst only] The MRU data provide a basis for interpreting whether shaped catalysts yield heterogeneous catalysts with robust, long-term performance with no or minimal loss of activity and / or selectivity, which can be regenerated by appropriate methods, but the time between regenerations should be as long as possible.
[0145] To evaluate the performance of the supported shaped catalyst, a baseline was set with an unsupported shaped catalyst. Figure 8 shows the long-term ethane to ethylene conversion MRU data for shaped catalyst 1.2SB tablets with only MoVTeTaOx catalyst. The shaped catalyst 1.2SB tablets were prepared as described in Example 5, and the MRU experiments were performed with the following parameters as described in the detailed description:
[0146] The experimental results shown in Fig. 8 were taken at 470℃ and 6922GHSV(hr -1 ), 5.462WHSV(hr -1 ) The MRU procedure was carried out as described herein. For shaped catalyst 1.2SB tablet, the initial ethane conversion at time=0 was 47.4 mol% and increased to 49.6 mol% at about time=71 hours. From timestamp about 71 hours to the end of the run at about 240 hours, a loss of Δ-0.09 mol% ethane conversion was observed during this 169 hour period, which corresponds to a loss of 0.0005 mol% absolute ethane conversion / hour.
[0147] Figure 9 shows the long-term ethylene selectivity test results for shaped catalyst 1.2SB tablets. The experimental results shown in Figure 9 were collected at 470 °C. As shown in Figure 9, the selectivity of shaped catalyst 1.2 remained relatively constant over the test period, with an ethylene selectivity of about 89 mol%. Thus, these tablets exhibited high selectivity with minimal loss over time, indicating their suitability for the oxidative dehydrogenation of ethane.
[0148] [Example 8: MRU data, molded catalyst 1.3SB] 10 and 11 show the MRU data plots for MoVTeTaOx supported shaped catalyst 1.3SB tablets. The shaped catalyst 1.3SB tablets were prepared as described in Example 5.
[0149] Conversion and selectivity results for the long-term test of supported MoVTeTaOx shaped catalyst 1.3 tablets are shown in Figures 10 and 11, respectively. The MRU experiment was performed as described in the detailed description, with the following modifications: The long-term experiment for shaped catalyst 1.3 was run for a total of about 2176 hours at process temperatures of 450°C (first 263 hours) and 460°C (remaining 1913 hours). Figure 10 shows the results of a long-term ethane conversion test for MoVTeTaOx shaped catalyst 1.3SB tablets. The test was run for a total of about 2176 hours at process temperatures of 450°C (first 263 hours) and 460°C (remaining 1913 hours). The experiment was run in three stages, as described herein: an equilibration period at 450°C (triangles), higher conversion at 460°C before shutdown (diamonds), and higher conversion at 460°C after shutdown (circles). The total data represents a 2934 GHSV (hr -1 ) (including the volume of the catalyst and support) and 5.462 WHSV (hr -1 ) (catalyst weight only, not including support). The outage was conducted as a routine safety system test. However, these three data periods can be used to demonstrate the properties of the molded catalyst 1.3 tablets.
[0150] From FIG. 10, it can be seen that the MoVTeTaOx supported shaped catalyst 1.3SB exhibited subtle deactivation trends. However, this MRU experiment was unique in that the process conditions were pushed such that the catalyst converted nearly the entire amount of the oxygen feed. Higher temperatures result in higher conversions, and therefore more oxygen consumed to produce ethylene. With no oxygen remaining, the catalyst may be starved of the oxygen needed to complete the catalytic cycle, damaging it. This was done to purposely exaggerate the catalyst deactivation and determine whether regeneration after deactivation is possible. As shown herein, the shaped catalyst 1.3SB tolerates high conversion / low oxygen conditions without damage. Thus, industrial processes can be run at higher conversions with less oxygen in the outlet gas product, resulting in less downstream equipment and / or processing required to remove the remaining unreacted oxygen. Additionally, this experiment demonstrates that conditions with higher oxygen consumption can result in faster or slower deactivation compared to other experiments shown herein. Without wishing to be bound by theory, it is hypothesized that high oxygen consumption leads to faster deactivation of the catalyst, similar to what is observed for catalysts containing MoVTeNbOx.
[0151] At a process temperature of 450° C., the ethane conversion of MoVTeTaOx supported shaped catalyst 1.3SB tablet was 48.4 mol% at time=0 hours and 51.9 mol% at about time 24 hours, shown as the “Equilibrium Period” in FIG. 10. From about time 24 hours (51.9 mol% ethane conversion) to about time 260 hours (50.8 mol% ethane conversion), the ethane conversion changed by Δ−1.1 mol% absolute over this 236 hour period, which corresponds to a loss of 0.0085 mol% absolute ethane conversion / hour.
[0152] At timestamp approximately 283 hours, the MRU experimental process temperature was increased from 450°C to 460°C, increasing the ethane conversion to 54.6 mol%. At 54.6 mol% conversion, the amount of oxygen in the product was measured by GC to be 0.53 mol%. It has previously been determined that MoVTeNbOx catalysts can deactivate when the amount of oxygen in the product gas stream is less than 1 mol%. In Figure 10, this data is labeled as "Before Safety System Shutdown."
[0153] The experiment was run uninterrupted for 76 hours from about 283 hours to about 359 hours, after which a planned shutdown was performed to cool the MRU unit from 460°C to room temperature under nitrogen gas purging. During the 76 hours of uninterrupted operation, the ethane conversion changed by Δ-0.4 mol% ethane, which corresponds to a loss of 0.0053 mol% ethane absolute conversion / hour. Thus, it has been shown that these catalyst tablets are stable and the loss of ethane absolute conversion / hour is very small.
[0154] The MRU experiment resumed approximately seven days later. The experiment resumed at a temperature of 460 °C. From this point on, the timestamp was reset to t=0 hours for data comparison. In Figure 10, this data is labeled "After Safety System Shutdown."
[0155] After shutdown, from about time 0 hours (ethane conversion 52.7 mol%) to time 674 hours (ethane conversion 48.9 mol%), the ethane conversion changed by Δ3.8 mol% absolute, which corresponds to a loss of 0.0056 mol% ethane conversion absolute / hour.
[0156] The rate of deactivation trend before and after the safety system shutdown is essentially the same (approximately 0.005 mol% ethane conversion absolute / hour) even though the oxygen consumption is different. Before the system shutdown, the ethane conversion was high enough that the oxygen consumption (conversion) resulted in less than 1 mol% in the product gas. Absolute O2 was taken as a grab sample injected from the live process. After the shutdown, the oxygen in the product was mostly less than 1 mol% O2, but was close to this target in the range of 0.73 to 1.00 mol% O2. This was the case between timestamps 0 hours and 218 hours. After 218 hours, the amount of oxygen gas in the product gas was greater than 1 mol% O2. The similar results for the deactivation trend before and after operating the reactor at high oxygen gas consumption indicate that the deactivation trend is not related to the amount of oxygen consumed in the reactor.
[0157] This result provides insight into the mechanism of deactivation. Without wishing to be bound by theory, redox deactivation of molybdenum-based catalysts has been reported to be associated with over-reduction of the molybdenum oxide active centers. Over-reduced molybdenum sites can be converted to other states, irreversibly changing the active phase to an inactive crystalline phase. If redox deactivation is the primary mechanism of activity loss, it would be reasonable to expect that over-reduction of the catalyst occurred when process conditions were pushed to higher oxygen consumption. Over-reduction leads to a decrease in the overall activity of the catalyst bed, which is observed in the MRU data as an overall deactivation trend. However, if this mechanism of redox deactivation were dominant, an increase in oxygen consumption should accelerate the deactivation trend, which was not observed in this experiment. Therefore, another deactivation mechanism may be at work, e.g., sintering deactivation. Sintering deactivation is one of the most common deactivation mechanisms for heterogeneous catalysts. As shown herein, the catalyst is stable with minimal deactivation.
[0158] Figure 11 shows the long term ethylene selectivity test results for shaped catalyst 1.3SB tablets. The experiment was run in three stages as described herein: an equilibration period at 450°C (triangles), higher conversion at 460°C before shutdown (diamonds), and higher conversion at 460°C after shutdown (circles). The total data represents a GHSV of 2934 hr -1 ) (including the volume of the catalyst and support) and 5.462 WHSV (hr -1 ) (catalyst weight only, not including support). From FIG. 11 it can be seen that the selectivity remained relatively constant over the test period, with ethylene selectivity being about 88 mol%. Thus, these tablets show high selectivity with minimal loss over time, indicating that they are suitable for the oxidative dehydrogenation of ethane.
[0159] [Example 9: MRU data for molded catalyst 1.5SB] Figures 12 and 13 show the MRU data for MoVTeTaOx supported shaped catalyst 1.5SB tablets. Shaped catalyst 1.5SB was synthesized as described in Example 5. MRU experiments were performed with the following parameters as described in the detailed description. The experiments were performed for a TOS of 120 hours.
[0160] FIG. 12 shows the short-term ethane conversion test results for MoVTeTaOx supported shaped catalyst 1.5SB tablet. The experimental results in FIG. 12 were collected at 460° C. The total data was 3393 GHSV (hr -1 ) (including the volume of the catalyst and support) and 5.462 WHSV (hr -1 ) (catalyst weight only, not including support).
[0161] At t=0, the ethane conversion was 42.1 mol% and increased to 48.6 mol% after about 48 hours of TOS. From about 48 hours to the end of the run at about 120 hours, a Δ1.2 mol% ethane conversion was lost during this 72 hour period, which corresponds to a loss of about 0.0167 mol% absolute ethane conversion / hour.
[0162] FIG. 13 shows the long-term ethylene selectivity test results for MoVTeTaOx molded catalyst tablet 1.5SB. The experimental results shown in FIG. 13 were collected at 460° C. The total data was 3393 GHSV (hr -1 ) (including the volume of the catalyst and support) and 5.462 WHSV (hr -1 ) (catalyst weight only, not including support). As shown in Figure 13, the selectivity remained relatively constant over the test period, with ethylene selectivity of approximately 88 mol%. Thus, these tablets exhibited high selectivity with minimal loss over time, indicating that they are suitable for the oxidative dehydrogenation of ethane.
[0163] [Example 10: MRU data for molded catalyst 1.7SB] Molded catalyst 1.7SB was prepared as described in Example 5. The MRU process was run as described in the detailed description with the following parameters: Molded catalyst 1.7SB long-term experiment was run for a total of approximately 1197 hours at a process temperature of 470°C. In this experiment, intermittent air regenerations were performed to determine if the catalyst could be actively regenerated at set intervals. In this experiment, the "air" regeneration included a gas mixture of nitrogen and oxygen. The results showed that the catalyst had improved stability with active air regeneration at planned time intervals, t = 285 hours, 643 hours, and 980 hours. All air regenerations were performed at 380°C with a flow rate of 760 sccm and 10 volO2 / balance N2. All data was collected at 3323 GHSV (hr -1 ) (including the volume of the catalyst and support) and 5.462 WHSV (hr -1 ) (catalyst weight only, not including support).
[0164] Figure 14 shows the results of a long-term ethane conversion test. The results showed that the catalyst could be used without significant deactivation and could be regenerated. Another possible way to mitigate the observed deactivation would be to change the diluent (such as nitrogen) to steam and / or carbon dioxide.
[0165] Figure 15 shows the long-term ethylene selectivity test results for shaped catalyst 1.7SB tablets. As shown in Figure 15, the selectivity remained relatively constant over the test period, with the ethylene selectivity being about 87 mol%.
[0166] The results of the first air regeneration were good: first, there was no drop in selectivity, and ethylene remained stable at about 87 mol%. Second, activity was restored and remained high for a significant TOS period. Ethane conversion immediately after air regeneration was measured at 47.9 mol% at experiment t≈315 h, but increased to 49.0 mol% at t≈332 h. Comparing the ethane conversion of 49.0 mol% to 48.0 mol% before air regeneration corresponds to a positive improvement of Δ+1.0 mol% absolute. Advantageously, the conversion activity remained in the range of 48 mol% until the TOS timestamp of 621 h. The next regeneration was performed at TOS 643 h. Between 332 h and 643 h, the ethane conversion data were as follows: range = 47.0-50.0 mol%, mean = 48.4 mol%, standard deviation of the data = 0.78 mol% (47.6-49.2 mol%). Choosing an ethane conversion of 48 mol% as the end point of a TOS of 643 h and comparing it with the initial activity of 49.5 mol% at t=0 h, over this 614 h period, the ethane conversion changed by Δ-1.5 mol% absolute (minus the air regeneration time of about 29 h), which corresponds to a loss of 0.0024 mol% absolute ethane conversion / h. Thus, the catalyst can be successfully regenerated by air regeneration and can be used to maintain constant conversion of the process under normal operating conditions.
[0167] [Example 11: MRU data for molded catalyst 1.8SB] Molded catalyst 1.8SB was prepared as described in Example 5. The MRU process was run with the following parameters as described in the detailed description. The long-term run of molded catalyst 1.8 was run for a total of about 1032 hours at a process temperature of 420°C. Figure 16 shows the long-term ethane conversion of molded catalyst 1.8SB. As shown in Figure 16, the MoVTeNbOx supported molded catalyst 1.8 tablets showed very good stability.
[0168] At a process temperature of 420° C., the ethane conversion of the MoVTeNbOx shaped catalyst 1.8 tablets started at 44.4 mol% at time=0 hours and increased to 54.7 mol% at time≈47 hours. From about time 47 hours (54.7 mol% ethane conversion) to about time 357 hours (56.3 mol% ethane conversion), the ethane conversion changed by Δ+1.6 mol% absolute over this 310 hour period, which corresponds to an increase in ethane conversion absolute / hour of 0.0052 mol%. Overall, from time=0 hours to time≈357 hours, the ethane conversion changed by Δ+11.9 mol% absolute, which is a desirable result. The entire long-term test of the supported MoVTeNbOx shaped catalyst 1.8 tablets was carried out without air regeneration. At time ≈ 212 h there was an outage during which the feed gas was shut off and a nitrogen purge was started while the process was cooled down from 420 °C. However, this nitrogen purge period was short (< 1 h) and the resulting activity loss was short-lived, with the catalyst behavior fully recovering by time ≈ 233 h and improving by time ≈ 357 h. Starting at timestamp TOS 357 h, a subtle deactivation trend began. At timestamp TOS 1032 h, the ethane conversion was measured to be 54.4 mol% ethane conversion (average of the last four data points measured). The deactivation trend at about 1000 h was Δ-0.3 mol% absolute compared to the ethane conversion collected at time ≈ 47 h (54.7 mol% ethane conversion), based on the four-point average 54.4 mol% result obtained at the end of the experiment (t ≈ 1032 h). A delta-0.3 mol% absolute ethane conversion loss corresponds to a loss of 0.0003 mol% absolute ethane conversion / hour over the 985 hour experimental period.
[0169] The increase in ethane conversion was an unexpected result and indicates that the fumed silica support exhibits a synergistic effect with multiple shaped catalysts containing both MoVTeNbOx and MoVTeTaOx catalytic active phases.
[0170] Figure 17 shows the ethylene selectivity of the shaped catalyst 1.8SB tablets. As shown in Figure 17, the selectivity actually increased over the entire duration of the test, with the ethylene selectivity increasing from about 90 mol% to 92 mol%. This is also an unexpected, but desirable, result. Thus, these tablets exhibit high selectivity with minimal loss over time, indicating their suitability for the oxidative dehydrogenation of ethane.
[0171] Figure 18 shows the long-term ethylene selectivity tests of molded catalyst 1.7SB and molded catalyst 1.8SB overlaid on one plot. Table 7 summarizes the catalytic performance data for these molded catalysts. Both molded catalysts show little or no tendency to deactivate. The slight increase in the tendency to deactivate molded catalyst 1.7SB compared to molded catalyst 1.8SB is likely due to the higher temperature used in the analysis of molded catalyst 1.7SB.
[0172] [Table 7]
[0173] The following units of measurement are referred to in this disclosure: [Table 8]
[0174] The term "about" as used in this disclosure allows for a degree of variation in a value or range, for example, within 10%, within 5%, or within 1% of a stated value or the limits of a stated range.
[0175] As used in this disclosure, the term "substantially" refers to a majority or majority, such as at least about 50%, 60%, 70%, 80%, 90%, 95%, 96%, 97%, 98%, 99%, 99.5%, 99.9%, 99.99%, or at least about 99.999% or more.
[0176] The term "solvent" as used in this disclosure refers to a liquid that can dissolve a solid, another liquid, or a gas to form a solution. Non-limiting examples of solvents include silicones, organic compounds, water, alcohols, ionic liquids, and supercritical fluids.
[0177] As used in this disclosure, the term "room temperature" refers to a temperature between about 15°C and about 28°C.
[0178] The term "weight percent" (wt%) as used in this disclosure may be considered as the mass fraction or mass ratio of a substance relative to the entire mixture or composition. Weight percent may be a weight to weight ratio or a mass to mass ratio unless otherwise specified.
[0179] Although several embodiments of the present disclosure have been described, it will be understood that various modifications can be made without departing from the spirit and scope of the disclosure.
Claims
1. a catalytically active phase comprising a MoVTeTaOx catalyst; a support phase comprising fumed silica; wherein the catalytically active phase and the support phase form a heterogeneous mixture.
2. The composition of claim 1 further comprising a binder comprising a polymeric organic acid, an amine, or an alcohol.
3. The composition of claim 2 , wherein the binder comprises polyvinyl alcohol or polyethylene glycol, or both.
4. The composition of claim 3, wherein the binder comprises 60 to 80 wt % polyvinyl alcohol and 20 to 40 wt % polyethylene glycol.
5. The composition of claim 1 further comprising an inorganic binder comprising talc or calcium carbonate.
6. The composition of claim 1 further comprising sintering the composition to form a ceramic.
7. The composition of claim 1 further comprising a plasticizer comprising polyethylene glycol.
8. The composition of claim 1 further comprising a lubricant.
9. 9. The composition of claim 8, wherein the lubricant is 1 to 2 wt% of the composition, and the lubricant comprises graphite.
10. The composition of claim 1, wherein the fumed silica is from 5 to 95 wt % of the composition.
11. A compressed tablet comprising the composition of claim 1, having a density of 1.0 to 1.5 g / cm 3 A compressed tablet having a density of 0.1g / g.
12. A sintered ceramic catalyst comprising the composition of claim 1.
13. A method for producing a shaped catalyst, comprising the steps of: combining a catalytically active phase, a support phase, and a binder in an aqueous solvent to form an aqueous solution, wherein the catalytically active phase comprises MoVTeTaOx and the support phase comprises fumed silica; heating the aqueous solution to form a thick paste; drying the thick paste to evaporate the aqueous solvent and form a solid powder; milling the solid powder to form granules; compressing the granules to form a tablet; The above method.
14. 14. The method of claim 13, wherein the step of milling the solid powder to form granules comprises milling the solid powder to form granules, the granules having a diameter between 105 μm and 710 μm.
15. debinding the tablets, comprising heating the tablets to remove the binder; sintering the tablets, which comprises heating the tablets to coalesce into a densified solid; The method of claim 13 further comprising:
16. 16. The method of claim 15, wherein the step of debinding the tablet comprises heating the tablet to 200°C to 400°C at a rate of 1-2°C / min.
17. 16. The method of claim 15, wherein the step of sintering the tablet comprises heating the tablet to between 400°C and 600°C at a rate of up to 5°C / min.
18. A method for producing a shaped catalyst, comprising the steps of: combining a catalytically active phase, a support phase, and a binder in an aqueous solvent to form an aqueous solution, wherein the catalytically active phase comprises MoVTeTaOx and the support phase comprises fumed silica; heating the aqueous solution to form a thick paste; drying the thick paste to evaporate the aqueous solvent and form a solid powder; milling the solid powder to form granules; compressing the granules to form a tablet; debinding the tablets, comprising heating the tablets to remove the binder; sintering the tablets, which comprises heating the tablets to coalesce into a densified solid; The above method comprising the steps of:
19. 1. A process for the oxidative dehydrogenation of ethane comprising the steps of: flowing a feed gas into the microreactor unit, the feed gas comprising ethane, oxygen, and nitrogen; pressurizing a feed gas in a microreactor; contacting the feed gas with a shaped catalyst, the shaped catalyst comprising a catalytically active phase comprising a MoVTeTaOx catalyst and a support phase comprising fumed silica, the catalytically active phase and the support phase forming a heterogeneous mixture; heating the feed gas to 450°C to 470°C; recovering ethylene gas; The above method.
20. 20. The method of claim 19, wherein the feed gas has a molar ratio of ethane to oxygen of 1:0.5.